BUDGET 2026 PREVIEW The Consolidation Moment? - Amra, Rashaad (University of the Witwatersrand, Johannesburg, 2026)
South Africa enters the 2026 Budget cycle in a more stable, but still fragile, macroeconomic environment. Global growth has proven more resilient than expected, commodity prices have provided an uneven windfall, and domestic growth has stabilised after several volatile years. The formal adoption of a 3% inflation target has begun to anchor long-term expectations and lower borrowing costs, improving the arithmetic of debt stabilisation. Yet the foundations remain narrow. Global trade is slowing amid geoeconomic fragmentation, commodity price strength appears partly cyclical and sentiment-driven, and domestic growth remains modest and consumption-led rather than investment-driven. Unemployment remains unsustainably high and fiscal space constrained. The 2025 Medium-Term Budget Policy Statement (MTBPS) was characterised by a response to this altered macroeconomic environment. With lower projected nominal GDP — the cash value of economic activity, which determines tax collections — under the 3% inflation target, the entire fiscal framework had to adapt to a new monetary regime in order to preserve debt stabilisation. The adjustment burden fell predominantly on expenditure: non-interest spending was projected to decline in real terms in 2026, with real per capita core spending1 falling materially in the budget year. The MTBPS reaffirmed a path of fiscal consolidation aimed at achieving sustained primary surpluses — that is, budget surpluses before interest payments — and stabilising debt, but it did so through strong front-loaded expenditure compression. As the country approaches Budget 2026, the question is not merely whether stabilisation can be projected, but whether it can be implemented and sustained. The outlook for debt stabilisation has improved relative to a year ago, but its credibility ultimately hinges on the social feasibility of sustained expenditure compression, continued coalition consensus within the Government of National Unity (GNU), and the ability of Targeted and Responsible Savings (TARS) to convert expenditure reviews into durable fiscal space in a low-growth environment.
Keywords: BUDGET 2026; SDG-8: Decent work and economic growth; SDG-10: Reduced inequalities